KNOWLEDGE OF PATIENTS ABOUT THEIR RIGHTS IN HOSPITAL - Wiwin Nur Aeni (International Interdisciplinary Conference on Sustainable Development Goals, 2019)
Providing health services focuses on patients. The results of service will be optimal if the patient and family are aware of their rights so that service is in line with expectations, values, and culture. It is part of the patient's right to be fulfilled. The patient is entitled to a demand for something that is his personal need in accordance with justice, morality and legalistic. This study has three objectives, namely to find out the description of patient and family knowledge about the right to obtain information, the right to obtain services, and the right to make decisions in one nationally accredited hospital in Indramayu. This study used descriptive design. The population was the patients in four inpatient rooms with an average number of 660 per month. The sampling technique used accidental sampling. Sample size was calculated using formula Z with sample size 244 respondents taken proportionally from 4 inpatient room. The data collection tool used a questionnaire with 15 statements. The result of the research showed less knowledge about the right of information as much as 22,6% (55 respondents), less knowledge about right to get service as much as 13,9% (34 respondents), less knowledge about decision right as much 42,6% (104 respondents). The research conclusion was patient's knowledge about patient's rights is still less as much 20,1% (49 respondents). Research suggestions are expected to improve hospital information systems so that information media sources can be accessed easily and optimize the controlling of information delivery by officers